PERBANDINGAN HASIL BELAJAR KIMIA SISWA MENGGUNAKAN MODEL PEMBELAJARAN JIGSAW DAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN SCIENTIFIC PADA KELAS X IPA DI SMAN 3 KOTA BENGKULU TAHUN AJARAN 2018/2019 - Pepi Pepi; Hermansyah Amir; Rina Elvia (ALOTROP, 2019)
This study aims to compare the Think Pair Share (TPS) and Jigsaw learning models with the Scientific approach to the results and interest in learning chemistry in the mole concept material in class X MIPA SMAN 3 Kota Bengkulu. This research was carried out in January-April 2019. This type of research was a quasi-experimental study with a population of all classes of X MIPA totaling 180 students. How to obtain samples through normality and homogeneity tests through cluster random sampling technique, where two classes of research samples were obtained, namely Experiment 1 class which applied Think Pair Share (TPS) learning model and experimental class 2 which applied the Jigsaw learning model. Based on the results of the study it was concluded that the two learning models proved to be able to increase students' learning outcomes and interest in chemistry and reach KKM, namely 76 with the acquisition of the N-Gain Score in the Think Pair Share (TPS) learning model of 0.71 and in the Jigsaw learning model of 0, 79 where both values of N-Gain Score have a high category. The results of students' interest in learning chemistry in the experimental class 1 were 75.93% with good categories and the results of the learning interest in the experimental class 2 were 82.01% with very good categories. The results of hypothesis testing through t test on the cognitive aspect sig. (2-tailed) of 0.002 and in the affective aspect of 0,000. It states that there are significant differences in the results and interest in learning chemistry that apply Think Pair Share (TPS) and Jigsaw learning models with the Scientific approach.